Biological changes in auditory function following training in children with autism spectrum disorders - Nicol Trent; Hornickel Jane; Russo Nicole M; Zecker Steven; Kraus Nina (Behavioral and Brain Functions, 2010)
Abstract Background Children with pervasive developmental disorders (PDD), such as children with autism spectrum disorders (ASD), often show auditory processing deficits related to their overarching language impairment. Auditory training programs such as Fast ForWord Language may potentially alleviate these deficits through training-induced improvements in auditory processing. Methods To assess the impact of auditory training on auditory function in children with ASD, brainstem and cortical responses to speech sounds presented in quiet and noise were collected from five children with ASD who completed Fast ForWord training. Results Relative to six control children with ASD who did not complete Fast ForWord, training-related changes were found in brainstem response timing (three children) and pitch-tracking (one child), and cortical response timing (all five children) after Fast ForWord use. Conclusions These results provide an objective indication of the benefit of training on auditory function for some children with ASD.